Measurements of t(t)over-bar charge asymmetry using dilepton final states in pp collisions at root s=8 TeV - KAYA, MİTHAT (ELSEVIER, 2016)
The charge asymmetry in ttevents is measured using dilepton final states produced in ppcollisions at the LHC at root s = 8 TeV. The data sample, collected with the CMS detector, corresponds to an integrated luminosity of 19.5 fb(-1). The measurements are performed using events with two oppositely charged leptons (electrons or muons) and two or more jets, where at least one of the jets is identified as originating from a bottom quark. The charge asymmetry is measured from differences in kinematic distributions, unfolded to the parton level, of positively and negatively charged top quarks and leptons. The t (t) over bar and leptonic inclusive charge asymmetries are found to be 0.011 +/- 0.011 (stat) +/- 0.007 (syst) and 0.003 +/- 0.006 (stat) +/- 0.003 (syst), respectively. These results, as well as charge asymmetry measurements made as a function of the invariant mass, rapidity, and transverse momentum of the t (t) over bar system, are in agreement with predictions of the standard model. (C) 2016 The Author(s). Published by Elsevier B.V.
Keywords: CMS; Physics; Top; Charge asymmetry; QUARK PAIR PRODUCTION; DECAY; TEVATRON